Simulační techniky oftalmopedické Metodické texty k projektu MUNI 4.0. Pedagogická fakulta, studijní program Logopedie (Bc.) - Vrubel, Martin (Masaryk University Press, 2019)
Title in English: Simulation techniques - Education of people with visual impairments This handbook creates support for students of the course Simulation techniques - Education of people with visual impairments. This text is divided into three logical, interconnected parts. In the first part, students are acquainted with the topic of the influence of functional vision on the pupil's work in the classroom. The second part deals with the problems of spatial orientation, independent movement and removing barriers. The third part contains practical exercises in which students will try the specifics of working with pupils with visual impairments at school. The aim of the text is to support positive attitudes towards pupils with visual impairments.